Economic Analysis of Factors Affecting Sudanese Live Sheep Exports to Kingdom of Saudi Arabia (University of Khartoum Journal of Agricultural Sciences, 2023)
The major objective of this paper was to analyze the effects offactors responsible for the exported quantity of Sudanese live sheep to themarket of the Kingdom of Saudi Arabia (KSA). For this end, data onexported quantities, import prices, competitors' prices, exchange rate andSaudi chilled mutton imports was used. Multiple regression analysis wasused for estimating the effect of these factors via a transformedgeneralized Cobb-Douglas function. Among the four hypothesizedvariables, only import price and exchange rate were having significanteffect on exported live sheep quantities. Consistent with the economiclogic, the former was having an elastic effect while the latter had aninelastic effect. The other two variables with insignificant effect werecompetitors' price and KSA imported chilled mutton. All four variablesexerted increasing returns to scale to the Sudanese exported live sheepquantity. To increase live sheep exports to the Saudi market, the paperrecommends improvement of quality control measures, reduction ofproduction cost as well as minimizing the tax margins levied by thedifferent local governments involved, adopting long term contracts infuture markets and have Sudan Central Bank adopt exchange rate policymeasures to encourage investments in this foreign trade business.